ANALISIS PERANAN SEKTOR INDUSTRI PENGOLAHAN BANTEN DALAM PEREKONOMIAN BANTEN DAN NASIONAL - Saeful Hidayat (Jurnal Bina Bangsa Ekonomika, 2022)
The business field or processing industry sector is a strategic sector in the banten economy. In addition to dominating the economy and absorbing a large number of workers, processing industry products are also the main commodities for Banten's foreign exports. This study generally aims to analyze the role of banten processing industry business fields in the scope of the Banten and National economy, using the IRIO Indonesia 2016 Table. Specifically, the purpose of his research is to analyze the relationship between the processing industry sector and other sectors in the Banten economy, as well as its relationship with the national economy. In addition, a measurement of the role of processing industry business fields is also carried out through the identification of leading sectors and analysis of multiplier numbers. The results showed that the sub-fields of the food and beverage industry, the textile and apparel industry, as well as the paper and paper goods industry, printing and reproduction of recording media, have a very high forward and backward linkage with other sectors in Banten, thus becoming Banten's leading sector. However, of these three sub-fields of business, only the paper and paper goods industry, printing and reproduction of recording media also play a role as the national leading sector